Architectural innovation manual - Tang Art Design & Information Group Limited (Hong Kong : Tang Art Design & Information Group, 2011)
This book compiles more than one hundred projects (mainly foreign project) and categorizes these projects into categories of morphology innovation, structural innovation, material innovation, technology innovation, and function innovation according to the innovation concept in architecture. The innovation of these projects independently uses models of a certain kind of innovation or combines some classical models of several innovation patterns at the same time. We hope that the advancing innovation concepts in foreign architectures could bring more idea collision to the insiders of architectural industry and help them create more new and better architectures for the worlds development.
Keywords: Architecture and technology; Architecture -- Technological innovations Building materials